2020
DOI: 10.1038/s41419-020-2579-9
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA inhibits oral squamous cell carcinoma via reducing Akt-c-Myc signaling-mediated aerobic glycolysis

Abstract: Aerobic glycolysis is one of the hallmarks of human cancer cells. Overexpression of hexokinase 2 (HK2) plays a crucial role in the maintaining of unlimited tumor cell growth. In the present study, we found that the oral squamous cell carcinoma (OSCC) cells exhibited an aerobic glycolysis phenotype. Moreover, HK2 is highly expressed in OSCC patient derived-tissues and cell lines. Depletion of HK2 inhibited OSCC cell growth in vitro and in vivo. With a natural product screening, we identified Tanshinone IIA (Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 54 publications
1
51
0
Order By: Relevance
“…c-MYC, an important downstream transcription factor of the MAPK signaling pathway, is a protooncogene with an abnormal expression related to many cancers [36][37][38][39][40][41][42]. It also has been reported that reducing c-MYC can inhibit OSCC [43,44]. Moreover, the ubiquitination of DUSP6 can activate c-MYC, promoting the invasion of endometrial stromal cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…c-MYC, an important downstream transcription factor of the MAPK signaling pathway, is a protooncogene with an abnormal expression related to many cancers [36][37][38][39][40][41][42]. It also has been reported that reducing c-MYC can inhibit OSCC [43,44]. Moreover, the ubiquitination of DUSP6 can activate c-MYC, promoting the invasion of endometrial stromal cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of anti-ABCG2 monoclonal antibody EPI MBS+mAb and ultrasound treatment can reduce the clonal ability of MM CD138 − CD34 − CSC isolated from a human MM RPMI 8226 cell line and inhibit tumorigenesis in nude mice [ 32 ]. In addition, natural products are considered biocompatible and reliable treatments for human cancer [ 33 , 34 ]. Diallyl thiosulfinatecan enhances the inhibitory effect of dexamethasone on SP cells [ 35 ].…”
Section: Markers Of Mmscs and Drugs Targeting Themmentioning
confidence: 99%
“… Kim et al (2020) have found that genipin can increase the expression of p53 and DRAM, induce apoptosis and autophagy, and enhance the sensitivity of AGS and MKN45 gastric cancer cell lines to OXA. Tanshinones are a group of abietane diterpenes from the TCM Danshen and have exhibited anticancer activities in vitro and in vivo ( Li M. et al, 2020 ). Xu Z. et al (2018) have reported that tanshinone IIA can reduce the expression of multidrug resistance protein 1 (MRP1) and inhibit the efflux of adriamycin (ADM).…”
Section: Modulatory Effects Of Autophagy Inhibitors and Activators Onmentioning
confidence: 99%